2012
DOI: 10.1007/978-3-642-34450-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional expansion methods: grand challenges

Abstract: We discuss the source of errors in semiempirical density functional expansion (VE) methods. In particular, we show that VE methods are capable of well-reproducing their standard Kohn-Sham density functional method counterparts, but suffer from large errors upon using one or more of these approximations: the limited size of the atomic orbital basis, the Slater monopole auxiliary basis description of the response density, and the one-and two-body treatment of the coreHamiltonian matrix elements. In the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…While the limitation to second order effects at first may seem overly restrictive, recent work e.g. by Giese and York, 41,42 has shown that carefully conducted second order expansions can yield polarization responses and even geometries nearly indistinguishable from the full KS DFT case. In section 2 we show ACKS2 to go even one step further, yielding excellent agreement not only for the induced molecular dipole moments but also the polarization energy.…”
Section: Theoretical Background Of the Acks2 Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the limitation to second order effects at first may seem overly restrictive, recent work e.g. by Giese and York, 41,42 has shown that carefully conducted second order expansions can yield polarization responses and even geometries nearly indistinguishable from the full KS DFT case. In section 2 we show ACKS2 to go even one step further, yielding excellent agreement not only for the induced molecular dipole moments but also the polarization energy.…”
Section: Theoretical Background Of the Acks2 Methodsmentioning
confidence: 99%
“…Similar failures can be found for straightforward applications of density functional tight binding DFTB2. 42 Both of these can be substantially improved though, by coupling the respective ground state electronic structures to carefully parametrized implementations of the chemical potential equalization (CPE). A single post-processing step of CPE, for example, yields an RME of 12% and 3% for induced dipole moments and molecular polarizabilties, respectively for MNDO, 47 and 5% for molecular polarizabilities in DFTB2.…”
Section: Comparison To Other Polarizeable Methodsmentioning
confidence: 99%
“… 26 , 27 Therefore, despite the tremendous progress in ab initio QM and QM/MM methods, it remains meaningful to explore further development of the semiempirical type of QM methods. 28 31 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the description of electrostatic fluctuations in weakly bound systems may be poorly described via the Mulliken charges. Improvement of electric dipole polarizabilities and polarization energies in the framework of DFTB2 [68] and DFTB3 [53,69] was proposed within the so-called Chemical Potential Equalization (CPE) scheme. The principle is based on an expansion of the energy as a response to the field in the vicinity of the field-less DFTB density…”
Section: Non-covalent Interactionsmentioning
confidence: 99%